Engaging Jungian function-orientations in a hermeneutical community: Exploring John 11: 1–17 - Francis, Leslie J. (HTS teologiese studies, 2023)
Working within the sensing, intuition, feeling, thinking (SIFT) approach to biblical hermeneutics, the present study invited a hermeneutical community of 23 type-aware participants to explore the account of the Death of Lazarus as reported in John 11: 1–17 within type-alike groups differentiated according to the participants’ dominant function-orientation. Five groups were constituted differentiating: introverted sensing, introverted intuition, extraverted intuition, introverted and extraverted feeling and introverted and extraverted thinking. These five groups generated distinctive readings of the narrative that were characteristic of the individual type preference.Contribution: The SIFT method, situated within the reader perspective approach to biblical hermeneutics, is concerned with attending to the influence exerted by the psychological type profile of the reader on interpreting the text. The present study goes beyond previous work by comparing the responses of five hermeneutical communities (each distinguished by a different dominant function-orientation) to the same passage of scripture.